IMPLEMENTATION OF DPSIR FRAMEWORK IN THE MANAGEMENT OF THE ALMYROS BASIN, MAGNESIA PREFECTURE - Lyra, A.; Pliakas, F.; Skias, S.; Gkiougkis, I. (Bulletin of the Geological Society of Greece, 2016)
In this paper, the implementation of the framework DPSIR is presented in the coastal part of the Almyros Basin, Magnesia Prefecture. The procedure included the use of previous relevant geological, hydrological, hydrogeological and management studies, regarding the study area, the results of which are classified and assigned to the driving forces, pressures, states, impacts and responses of the DPSIR method for the area under investigation. The approach concluded to an interesting visualization of the current situation of the urban and natural environment of the study area, promoting the recognition of problems arising from the intervention of the human factor and directing environmental actions towards a rational water resources management in the wider region.